2019
DOI: 10.5194/bg-16-663-2019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling anaerobic soil organic carbon decomposition in Arctic polygon tundra: insights into soil geochemical influences on carbon mineralization

Abstract: Abstract. Rapid warming of Arctic ecosystems exposes soil organic matter (SOM) to accelerated microbial decomposition, potentially leading to increased emissions of carbon dioxide (CO2) and methane (CH4) that have a positive feedback on global warming. Current estimates of the magnitude and form of carbon emissions from Earth system models include significant uncertainties, partially due to the oversimplified representation of geochemical constraints on microbial decomposition. Here, we coupled modeling princi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 71 publications
(106 reference statements)
2
29
0
Order By: Relevance
“…These bacteria are known to ferment complex organic matter into acetate, H 2 , and CO 2 (Rojas et al, 2018), and have been previously shown to co-occur with methanogens in environments with degraded OM (Baldwin et al, 2015). Given that this fermentation of complex OM into substrate for methanogenesis is the rate-limiting step in Arctic anaerobic C mineralization (Zheng et al, 2019), it is possible that the degradation of unsaturated high oxygen compounds we observed in our anaerobic incubation correlates to fermentation of OM by Bacteroidales and Clostridales into substrate for methanogenesis.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 99%
“…These bacteria are known to ferment complex organic matter into acetate, H 2 , and CO 2 (Rojas et al, 2018), and have been previously shown to co-occur with methanogens in environments with degraded OM (Baldwin et al, 2015). Given that this fermentation of complex OM into substrate for methanogenesis is the rate-limiting step in Arctic anaerobic C mineralization (Zheng et al, 2019), it is possible that the degradation of unsaturated high oxygen compounds we observed in our anaerobic incubation correlates to fermentation of OM by Bacteroidales and Clostridales into substrate for methanogenesis.…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 99%
“…The model is archived at https://doi.org/10.5440/1430703 (Zheng et al, 2018c), with a detailed description of model implementation, input files, and various sensitivity analyses described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…How quickly frozen soil organic matter (SOM) will be mineralized, and how much permafrost C will be released to the atmosphere following thaw, is highly uncertain. Earth system models project 27-508 Pg carbon release from the permafrost zone by 2100 under current climate forcing (Zhuang et al, 2006;Koven et al, 2015;MacDougall et al, 2012;Schaefer et al, 2014). Understanding environmental dependencies of SOM decomposition is therefore essential for reducing model uncertainties and improving predictions of future climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for all the factors affecting Fe redox dynamics discussed above, for example, detailed soil biogeochemistry (Zheng et al, 2019), microbial growth and decay, C cycling, vegetation dynamics, and soil water balance (e.g., Calabrese & Porporato, 2019), would make it hard to analyze the interaction between internal and external controls, because these many interacting variables could overshadow the role of Journal of Geophysical Research: Biogeosciences 10.1029/2020JG005894 external forcings. Therefore, here we focus on potential Fe reduction rates, which are achieved under nonlimiting availability of labile C and microbial populations and their upper bound.…”
Section: Minimalist Model and Upper Bounds On Fe Reduction Ratesmentioning
confidence: 99%